Analyzing Public Perception on Integrating Ride-Hailing with Emergency Health Services - Tubagus Robbi Megantara; Rizki Apriva Hidayana; Indah Mauludina Hasanah (International Journal of Business, Economics, and Social Development, 2026)
Traditional Emergency Health Services (EHS) face numerous challenges, including response time efficiency. The integration of ride-hailing platforms offers an innovative solution, yet public perception of this concept remains underexplored. This study investigates public perception through a quantitative survey of 100 respondents, analyzed as a whole and as two subgroups: those with prior EHS experience (n=48) and those without (n=52). The results reveal exceptionally strong and broad public support for this integration. A key finding is a significant "experience gap": respondents with prior EHS experience demonstrate confident demand with less hesitation, while non-users show more theoretical support with higher neutrality, particularly regarding personal adoption. Despite this difference, both groups show a high consensus on fundamental requirements such as patient safety, driver competency, and the availability of medical equipment. This study concludes that there is high social viability for integrating ride-hailing and EHS. The findings provide a clear mandate for stakeholders to proceed with innovation, on the condition that system development prioritizes the safety and reliability standards expected by the public. This research lays the groundwork for the next stage: the development of mathematical models for a decision-support system to translate this concept into an effective and trustworthy solution. Keywords: ride-hailing, emergency health services, public perception, mathematical modeling, decision-support systems.